Strategies for Reducing the Consequences of the Seasonality in Tourism - Dimitrova, Stela (Research Papers, 2018)
Seasonality is a universal factor in tourism and is often seen as a problem, especially in economic terms. This article sets out its features and offers different ways to deal with it, aiming at giving a clear idea of the possibilities of attracting customers and increasing the attractiveness of the tourist product. All this determines the topicality and significance of the studied issues, which give rise to the need to seek adequate solutions to the problem of tourism seasonality as well as the resulting challenges facing the tourism industry.